2021
DOI: 10.1002/ecy.3262
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sampling design for spatial capture–recapture

Abstract: Spatial capture–recapture (SCR) has emerged as the industry standard for estimating population density by leveraging information from spatial locations of repeat encounters of individuals. The precision of density estimates depends fundamentally on the number and spatial configuration of traps. Despite this knowledge, existing sampling design recommendations are heuristic and their performance remains untested for most practical applications. To address this issue, we propose a genetic algorithm that minimizes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Efford and Boulanger ( 2019 ) proposed that an evaluation of expected sample sizes of individuals and recaptures using simulations can be related to expected precision, which can be used to inform optimal SCR sampling design. Similarly, Dupont et al ( 2021 ) further identified a genetic algorithm that optimized an objective function related to estimator precision to more quickly identify an optimal design based on a goal of maximizing the number of individuals detected, the number of spatial recaptures, or a balance of these two criteria. Finally, multiple study areas can be used to better capture variability in landscape features when landscape heterogeneity in density is being evaluated or when inference across a larger landscape is of interest (Short Bull et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efford and Boulanger ( 2019 ) proposed that an evaluation of expected sample sizes of individuals and recaptures using simulations can be related to expected precision, which can be used to inform optimal SCR sampling design. Similarly, Dupont et al ( 2021 ) further identified a genetic algorithm that optimized an objective function related to estimator precision to more quickly identify an optimal design based on a goal of maximizing the number of individuals detected, the number of spatial recaptures, or a balance of these two criteria. Finally, multiple study areas can be used to better capture variability in landscape features when landscape heterogeneity in density is being evaluated or when inference across a larger landscape is of interest (Short Bull et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical survey designs that use clusters of camera stations such that spatial recaptures can occur within widely spaced groups of cameras could extend the spatial area sampled by survey grids ( Efford and Fewster 2013 ; Sun et al 2014 ). Optimization criteria and functions are available to help predict the most informative detector station layouts for a given survey area ( Dupont et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate this in the present study, but sambar deer density estimation at site BL may have benefited from this approach. Clustered survey designs can increase the area covered by a camera trap survey and the number of individuals detected without biasing spatial capture–recapture parameter estimates ( Sun et al 2014 ; Efford and Boulanger 2019 ; Dupont et al 2021 ). The optimal allocation of effort across cluster size and number of clusters can be explored using optimization algorithms and simulations ( Sun et al 2014 ; Efford and Boulanger 2019 ; Dupont et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of traps may determine the number of individuals encountered and the frequency of detections, whereas the trap spacing may determine the frequency and spatial range of spatial recaptures. In the sampling design phase, the choice between deploying an extensive trapping array (i.e., large area, low trap density) versus an intensive array (i.e., small area, high trap density) may have substantial implications for detection probability and number of spatial recaptures (Wilton et al 2014, Dupont et al 2021. While empirical evaluations of SCR design are lacking, simulation studies suggest that SCR methods perform well when the trapping area is larger than a home range, and when trap spacing is close to 2-3σ, which, in theory, equates roughly to the radius of a typical home range, making spatial recaptures possible (Sollmann et al 2012, Sun et al 2014.…”
Section: Introductionmentioning
confidence: 99%